2019
DOI: 10.1093/biolre/ioz134
|View full text |Cite
|
Sign up to set email alerts
|

COX2 is induced in the ovarian epithelium during ovulatory wound repair and promotes cell survival†

Abstract: The ovarian surface epithelium (OSE) is a monolayer of cells surrounding the ovary that is ruptured during ovulation. After ovulation, the wound is repaired, however, this process is poorly understood. In epithelial tissues, wound repair is mediated by an epithelial-to-mesenchymal transition (EMT). Transforming Growth Factor Beta-1 (TGFβ1) is a cytokine commonly known to induce an EMT and is present throughout the ovarian microenvironment. We, therefore, hypothesized that TGFβ1 induces an EMT in OSE cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…WNT4 and WNT5a have been found to play crucial roles during follicle development and ovulation [23][24][25] and we have explored here their roles during ovulatory wound repair. Our evidence suggests WNT5a, but not WNT4, regulates cell morphology, proliferation, and migration and stimulates the expression of Cd44, Vim, Snail, Ptgs2 and Alcam, all markers of mesenchymal cells 26,32,33 , implicating WNT5a as a possible autocrine regulator of epithelial cells undergoing EMT. Previously, Wnt5a was identified as a gene whose expression was increased by TGFβ1 in mammary epithelial cells, and is required for the TGFβ1-mediated inhibition of ductal extension in vivo and branching in vitro 34 .…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…WNT4 and WNT5a have been found to play crucial roles during follicle development and ovulation [23][24][25] and we have explored here their roles during ovulatory wound repair. Our evidence suggests WNT5a, but not WNT4, regulates cell morphology, proliferation, and migration and stimulates the expression of Cd44, Vim, Snail, Ptgs2 and Alcam, all markers of mesenchymal cells 26,32,33 , implicating WNT5a as a possible autocrine regulator of epithelial cells undergoing EMT. Previously, Wnt5a was identified as a gene whose expression was increased by TGFβ1 in mammary epithelial cells, and is required for the TGFβ1-mediated inhibition of ductal extension in vivo and branching in vitro 34 .…”
Section: Discussionmentioning
confidence: 67%
“…Previously, Wnt5a was identified as a gene whose expression was increased by TGFβ1 in mammary epithelial cells, and is required for the TGFβ1-mediated inhibition of ductal extension in vivo and branching in vitro 34 . We have recently shown that treating primary cultures of OSE cells with TGFβ1 induced an EMT mediated by TGFβ1 signaling, and the transcription factor Snail was the only EMT-associated transcription factor tested that was increased by TGFβ1 26 . RNA-seq analysis of those cells showed that TGFβ1 up-regulates Wnt5a mRNA expression in OSE cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…COX2 expression increases following the LH surge and is expressed in the granulosa cells of pre-ovulatory follicles [52]. COX2 also plays a role following ovulation, in that it is upregulated during the EMT, a process involved in wound repair that is induced in the OSE following ovulation [53]. Based on its broad roles prior to ovulation and during wound repair, we questioned whether there were age-associated differences in COX2 expression in the ovary.…”
Section: Decreased Cox2 Expression May Be a Mechanism For Ovulatory Amentioning
confidence: 99%
“…We have previously demonstrated that mouse OSE (mOSE) cells undergo an EMT and acquire stem cell characteristics when exposed to TGFB1 10,16 . To confirm these findings, we first assessed the ability of TGFB1-treated mOSE cells to form self-renewing spheroids in suspension culture.…”
Section: Cd44 Is a Marker Of Emt-associated Stemness In Ose Cellsmentioning
confidence: 99%